Neutrophil elastase ameliorates matrix metalloproteinase-9 to promote lipopolysaccharide-induced acute lung injury in mice 1 - Guo,Yingfei (2016)
ABSTRACT PURPOSE: To investigate the regulatory roles of neutrophil elastase (NE) and matrix metalloproteinase-9 (MMP-9) in lipopolysaccharide (LPS)-induced acute lung injury (ALI) in mice. METHODS: To construct LPS-induced ALI mouse models, wild-type C57BL/6 mice were administered 5.0 mg/kg of LPS through endotracheal, and/or 1.0 mg/kg of ONO-5046, and/or 20.0 mg/kg of chemically modified tetracycline-3 (CMT-3) by gavage. The levels of MMP-9, tissue inhibitor of metalloprotease-1, interleukin (IL)-6 were detected by real time RT-PCR at 6 h, 24 h and 48 h, and tumor necrosis factor (TNF), lung wet-dry weight ratio, white blood cell (WBC) count and polymorphonuclear (PMN) count in bronchoalveolar lavage fluid (BALF) were tested at 48 h after administration. The 5-day survival analysis of the ALI mice was also performed. RESULTS: Both ONO-5046 and CMT-3, regardless of being used individually or combined, significantly reduced the levels of MMP-9, IL-6, and TNF in lung tissue as well as in BALF, and the WBC and PMN count in BALF. Combined treatment with ONO-5046 and CMT-3 remarkably improved the survival rate of ALI mice. CONCLUSION: Neutrophil elastase synergizes with matrix metalloproteinase-9 to promote and regulate the release of inflammatory mediators and the infiltration of inflammatory cells, consequently affecting the survival of lipopolysaccharide-induced acute lung injury mice.